Changeable sexualities and fluid masculinities: the intersections of sexual fluidity with hegemonic masculinity - Grave, Rita (2023)
This article explores the concept of sexual fluidity and its applicability to men’s sexual experiences by approaching the surveillance and control of hegemonic masculinity. We carried out semi-structured interviews with 15 participants aged between 20 and 53 who state having experienced sexual fluidity. The analysis conveys how sexuality is a work in progress while highlighting the intersections of masculinities and sexualities in a heteronormative, mononormative, sexually rigid, and hegemonically masculine social context. The results indicate the potential flexibility, malleability, and changeability of all sexual identities, orientations, and experiences when disengaging from a heteronormative approach in sexual relations.